Carl goes to daycare - Day, Alexandra (New York : Farrar Straus Giroux, 1993)
Carl the rottweiler takes charge when things take an unexpected turn at the day care center he is visiting.
Keywords: Day care centers -- Fiction; Dogs -- Fiction